2018
DOI: 10.2147/cmar.s171035
|View full text |Cite
|
Sign up to set email alerts
|

The clinical use of pretreatment NLR, PLR, and LMR in patients with esophageal squamous cell carcinoma: evidence from a meta-analysis

Abstract: Background and purposeThe relationship between neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and lymphocyte to monocyte ratio (LMR) and the prognostic and clinicopathological significance in patients with esophageal squamous cell carcinoma (ESCC) has been reported by many studies. However, inconsistent results have been presented. The current study aimed to investigate the prognostic and clinicopathological role of NLR, PLR, and LMR in patients with ESCC by meta-analysis.MethodsElig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 43 publications
2
88
1
Order By: Relevance
“…Nevertheless, the PLOS ONE bulk of literature have described that the higher LMR was a negative factor for the prognosis of diseases, such as gastric cancer [30] and early-stage Hodgkin lymphoma [31]. But a meta analysis study has suggested that the low LMR was associated with the poor outcome for patients with esophageal squamous cell carcinoma [32]. The results of the association of maternal LMR and pregnancy outcome is not exactly consistent with some studies.…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, the PLOS ONE bulk of literature have described that the higher LMR was a negative factor for the prognosis of diseases, such as gastric cancer [30] and early-stage Hodgkin lymphoma [31]. But a meta analysis study has suggested that the low LMR was associated with the poor outcome for patients with esophageal squamous cell carcinoma [32]. The results of the association of maternal LMR and pregnancy outcome is not exactly consistent with some studies.…”
Section: Discussionmentioning
confidence: 87%
“…The NLR was defined as the absolute neutrophil count divided by the absolute lymphocyte count within 2 weeks before the initial treatment. [4][5][6][7][8][9][10][11][12][13][14] The cutoff value calculated from the ROC curve, mean, tertile, or median in previous studies varied from 1.98-5; 4-11 thus, the standard cutoff value remains unknown. In the current study, the cutoff value was defined as the mean value of the NLR.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] The peripheral neutrophil-to-lymphocyte ratio (NLR) is a well-known inflammatory marker. Several authors have previously reported that a high NLR is significantly associated with poor survival in solid cancers, [4][5][6][7][8][9][10][11][12][13][14] including head and neck squamous cell carcinoma and breast cancer. However, whether the NLR affects prognosis in patients with parotid cancer remains unknown; therefore, the current study aimed to clarify this question.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the current situation of the lack of more reliable tumor prognostic indicators, NLR and PLR may provide information on patient prognosis. It is currently known that NLR and/or PLR may be associated with a variety of tumor prognosis, including non-digestive tumor NSCLC (37), breast cancer (38), ovarian cancer (39), Hodgkin lymphoma (40), prostate cancer (41), cervical cancer (42), nasopharyngeal carcinoma (28), and tumors of the digestive tract such as esophageal squamous cell carcinoma (43,44), gastric cancer (45), pancreatic cancer (46), and colorectal cancer (47).…”
Section: Discussionmentioning
confidence: 99%